Performance of Sanggar Melayu FORKAMKAT Performers through Anthropolinguistic Approach - Lubis, Tasnim; Br.Perangin-angin, Alemina; Moulita; Abus, Nurul Adilla Alatas; Abus , Abiyulail Alatas (Journal of Community Research and Service, 2025)
Performance on Sanggar Melayu FORKAMKAT was to facilitate their organization to be formal. The community development service team from Universitas Sumatera Utara facilitate the making notarial deeds and providing website as well as skills in managing it. The method used in implementing this work were ethnography and Forum Group Discussion (FGD). Based on the problem of Sanggar Melayu FORKAMKAT, they do not yet have an official site and technology-based and official management, therefore the community empowerment service teamfacilitates the creation of notarial deeds for partners and provides a website so that partners can manage it independently. In this way, the performance pattern of behavior of studio members changes to a behavior pattern of being official and more responsible in managing the studio which is a center of activity that is not only a medium for learning and channeling talent, but can also generate income for its members.